Gross Anatomical Observations on the Ileum of Prenatal Goat (Capra hircus) - Verma, Abhinov; Farooqui, MM; Prakash, Ajay; Pathak, Archana; Singh, Shriprakash; Gupta, Varsha; Sinha, Rupam (Indian Journal of Veterinary Anatomy, 2024)
The present investigation was done on the ileum of 36 non-descript goat embryos/foeti (irrespective of sex). Embryos/foeti were equally divided into three groups having 12 foeti in each group. The morphological observations of ileum were documented after performing dissection through ventral abdominal wall. The ileum was witnessed first time in the foeti at the age of 45 days of gestation. The thin peritoneal fold was observed first time between ileum and caecum at 82 days of gestation as ileocaecal fold. The ileocaecal fold showed a blood vessel and branching of blood vessel also noticed at its middle part at 145 days of gestation. The luminal surface of ileum showed projections indicating the presence of villi from 97 days of gestation under stereozoom microscope and distinct villi were noticed at 150 days of gestation. Statistical analysis revealed that there was highly significant increase in all measured biometrical parameters of ileum from early to late prenatal period. There was approximately twelve times increase in total length of ileum from group I to II, while, three times increase from group II to III, which revealed that maximum growth took place from group I to II. The average diameter of ileum increased 3.9 times and 2.3 times from group I to II and from group II to III, respectively.